2014
DOI: 10.1111/1753-0407.12221
|View full text |Cite
|
Sign up to set email alerts
|

Alanine transferase: An independent indicator of adiposity related comorbidity risk in youth

Abstract: Even within the normative range, ALT levels were significantly correlated with anthropomorphic and biochemical risk factors for adiposity-related co-morbidities in youth. Therefore, because ALT is correlated with dyslipidemia, insulin resistance, and central fat distribution, it might also serve as a marker of risk for adiposity-related co-morbidities beyond NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…ALT is connected with adiposity and CVD risk factors [39]. A positive association between ALT and trunk fat independent of trunk and extremity lean mass was found in one study [16], while central adiposity along with generalized adiposity is reported by others [5]. Furthermore, ALT was not elevated in otherwise healthy obese people in a clinical study with limited number of participants contrasting our results [40].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…ALT is connected with adiposity and CVD risk factors [39]. A positive association between ALT and trunk fat independent of trunk and extremity lean mass was found in one study [16], while central adiposity along with generalized adiposity is reported by others [5]. Furthermore, ALT was not elevated in otherwise healthy obese people in a clinical study with limited number of participants contrasting our results [40].…”
Section: Discussioncontrasting
confidence: 59%
“…Alanine transaminase (ALT) is associated with obesity [1, 2], cardiovascular disease (CVD), and CVD-related mortality [35]. Clinical and population studies have related ALT with insulin resistance, metabolic syndrome, and type 2 diabetes [68].…”
Section: Introductionmentioning
confidence: 99%
“…[45] In our study, serum TNF-α levels were higher in the individuals with NAFLD than in those without NAFLD, but TNF-α did not correlate with ALT, HOMA-IR, adiponectin, or any other parameter, in agreement with previous reports in obese patients. [39] These findings might indicate that the TNF-α system is activated in NAFLD, but its relationship with insulin resistance and other metabolic risk factors remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The main indicator to enroll further diagnostics for liver injury in clinician’s daily routine are liver transaminases. Thus, current normal values might miss a significant amount of individuals already developing chronic metabolic liver disease and presenting with transaminase values in the upper normal levels 32 33 .…”
Section: Discussionmentioning
confidence: 99%